The Story upon a Hill : The Puritan Myth in Contemporary American Fiction - Leise, Christopher, 1978- (Book collections on Project MUSE., 2017)
"A timely study of contemporary American literature that highlights the everpresence of Puritan myths in American identity and culture"--